Detecção do gene do vírus da hepatite B e antigeno CA 125 para o tumor do ovário: uma plataforma especifica para diagnóstico point-of- care - Castro, Ana Cristina Honorato de (2016)
The ovarian cancer is a gynecologic cancer that originates in the female reproductive organs. Usually the diagnosis is made late, when the disease is already at an advanced stage, which reflects in the high rate of mortality. It is a silent disease, such as hepatitis B disease caused by hepatitis B virus (HBV), highly infectious and difficult to treat due to liver inflammation. Perform early diagnosis and monitoring is extremely important since both diseases lead to death numerous people annually. However, traditional diagnostic tests are expensive, time consuming and not confirmatory, and therefore the development of new detection and monitoring strategies is relevant to public health. One of the best alternatives are biosensors, chemical sensors which are recognition system is provided with biomolecules performing biochemical reactions. They have advantages over existing methods, such as low cost, high selectivity and sensitivity, real-time detection and immediate response. Assessing the severity of cases of ovarian cancer and high rates of hepatitis B infection, this study aimed to develop two electrochemical biosensors with unique and innovative features. To CA125 (carbohydrate antigen 125) detection, tumor marker used in the diagnosis and monitoring of ovarian cancer, was built an electrochemical immunosensor employing screen-printed electrodes functionalized with poly (3-hydroxyphenylacetic) and potassium ferrocyanide solution. The sensor has proven to be a versatile platform with high selectivity, interesting for diagnosis and monitoring of cancer. For the analysis of hepatitis B was built a genosensor using graphite electrodes functionalized with poly (4-aminophenol) as platform and ethidium bromide as electrochemical indicator of hybridization. The developed platform has unique and innovative features with advantages inherent to its applicability in plasma samples, important in the early diagnosis of the disease.